Minimally invasive treatment of gynecomastia by ultrasound-guided vacuum-assisted excision: report of a case series - Couto, Henrique Lima; Valadares, Carolina Nazareth; Pellegrini Junior, Osmar; Oliveira, Tereza Cristina Ferreira de; El Bacha, Patricia Martins Gomes; Ferreira, Shirley das Graças (Mastology, 2021)
Introduction: Gynecomastia (GM) is a benign proliferation of glandular breast tissue in men. Some cases need surgical intervention. Traditional open surgery by semicircular inferior periareolar incision is the most common surgical approach. In order to obtain better esthetic results, some alternatives to open surgery have been proposed, such as liposuction, endoscopic mastectomy, and vacuum-assisted excision (VAE). Objective: To describe the technical surgical approach of ultrasound-guided VAE of GM and its results from a case series. Method: This is an evaluation of seven GM cases submitted to ultrasound-guided VAE with a 10G needle using the ENCOR ® BD whole circumference automated breast biopsy system in Redimasto – Redimama, a Brazilian breast center. The result was considered good or satisfactory when it showed minimal remaining gland, good symmetry, no retraction, necrosis, hypertrophic scar, or displacement of the nipple-areola complex. All patients answered a questionnaire to evaluate their satisfaction and perception of the procedure. Results: Seven (7) patients with Simon grade 1 and 2 bilateral GM underwent ultrasound-guided VAE. No case of displacement, necrosis, or retraction of the nipple-areola complex, post-procedure bleeding, infection, skin necrosis, or asymmetry was detected. No patient reported decrease or change in nipple sensation or erection. All patients had bruises and hematomas that spontaneously resolved within 30 days. All results were considered good or excellent by patients and surgeons. Conclusion: Minimally invasive ultrasound-guided VAE is an excellent alternative for the treatment of GM. It is better indicated for Simon grade 1 and 2 GM, with good and excellent esthetic results, small scar, and low rates of nipple and areolar complications. It allows an outpatient procedure with low morbidity (local anesthesia) and fast recovery.